N/A: Anti-SARS-CoV-2 antibodies in healthcare workers - Lippi, Giuseppe; Salvagno, Gian Luca; Henry, Brandon Michael; Pighi, Laura; De Nitto, Simone (Journal of Medical Biochemistry, 2021)
Background: This study aimed at monitoring the kinetics of serum total anti-SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) antibodies in a cohort of healthcare workers after voluntary vaccination with Pfizer-BioNTech coronavirus disease 2019 (COVID-19). Methods: The study population consisted of 787 healthcare workers (mean age 44±12 years; 66% females), who received two 30 μg doses of Pfizer-BioNTech COVID-19 vaccine, 3 weeks apart. Venous blood was drawn before the first vaccine dose, immediately before the second vaccine dose, and then at 1, 3 and 6 months after the second vaccine dose. Serological testing employed the total anti-SARS-CoV-2 antibodies measurement with Roche Elecsys Anti-SARS-CoV-2 S chemiluminescent immunoassay. Results: The median serum levels of total anti-SARS-CoV-2 antibodies reached the peak (1762 KU/L) 1 month after the second vaccine dose, but tended to progressively decline at the 3-month (1086 KU/L) and 6-month (802 KU/L) follow-up points. Overall, the values after 3- and 6-months were 37% and 57% lower than the corresponding concentrations measured at the peak. No healthcare worker had total anti-SARS-CoV-2 antibodies below the method-dependent cut-off. The decline compared to the peak was more accentuated in baseline seropositive persons than in those who were baseline seronegative (74% vs. 52%) cohort. The 6-month post-vaccination anti-SARS-CoV-2 antibodies in subjects aged <65 years remained over 2-fold higher than that measured in those aged ≥65 years (813 vs. 343 KU/L). Conclusions: Gradual decline of total anti-SARS-CoV-2 antibodies occurred 6 months after Pfizer-BioNTech COVID-19 vaccination, though values remained higher than the method-dependent cut-off, with no case of seronegativization.